2018
DOI: 10.1371/journal.pone.0191245
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of a laminin-111 supplemented hyaluronic acid based hydrogel with minced muscle graft in the treatment of volumetric muscle loss injury

Abstract: Minced muscle autografting mediates de novo myofiber regeneration and promotes partial recovery of neuromuscular strength after volumetric muscle loss injury (VML). A major limitation of this approach is the availability of sufficient donor tissue for the treatment of relatively large VMLs without inducing donor site morbidity. This study evaluated a laminin-111 supplemented hyaluronic acid based hydrogel (HA+LMN) as a putative myoconductive scaffolding to be co-delivered with minced muscle grafts. In a rat ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 42 publications
(64 reference statements)
4
48
0
Order By: Relevance
“…Many of the tissue‐engineered scaffolds are either mechanically unsuitable or fail to enhance tissue‐resident stem cell activity . We are only aware of one other study where LM‐111 was delivered to the site of VML injury using hydrogels composed of hyaluronic acid and poly(ethylene glycol) . The study reported little to no cellular infiltration into the defect owing to the largely intact and undegraded hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the tissue‐engineered scaffolds are either mechanically unsuitable or fail to enhance tissue‐resident stem cell activity . We are only aware of one other study where LM‐111 was delivered to the site of VML injury using hydrogels composed of hyaluronic acid and poly(ethylene glycol) . The study reported little to no cellular infiltration into the defect owing to the largely intact and undegraded hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…132,133,[158][159][160][161][162] In a subsequent study, Corona and coworkers investigated a laminin-111 supplemented PEG-hyaluronic acidbased hydrogel as a delivery vehicle for minced muscle grafts for VML injuries. 163 At 8 weeks, the hydrogels were found to be wholly intact and did not support cellular infiltration into the defect site. The lack of cellular infiltration was associated 3 1255 with impaired muscle regeneration and function.…”
Section: Co-delivery Of Minced Muscle Grafts With Biomaterialsmentioning
confidence: 97%
“…In a subsequent study, Corona and coworkers investigated a laminin‐111 supplemented PEG‐hyaluronic acid‐based hydrogel as a delivery vehicle for minced muscle grafts for VML injuries . At 8 weeks, the hydrogels were found to be wholly intact and did not support cellular infiltration into the defect site.…”
Section: Biomaterials For Skeletal Muscle Regenerationmentioning
confidence: 99%
“…The permanent loss of muscle fibers is due to a fundamental loss of native regenerative elements required for skeletal muscle regeneration, such as the basal lamina and satellite cells [75][76][77]. Additionally, rodent and porcine animal models of VML injury have observed a heightened and prolonged inflammatory response [78,79] that significantly deviates from that observed in recoverable injury models such as ischemia reperfusion injury [80]. The prolonged inflammatory response after VML injury appears to drive extracellular matrix protein production and deposition, resulting in extensive compartmental fibrosis [81,82].…”
Section: Skeletal Muscle Regenerationmentioning
confidence: 99%